Response of calves to supplementation of forage legume - based concentrate diets - Bello, R. A. (2019)
Sixteen (16) crossbred (White Fulani, Muturu & Keteku) calves aged 7-10 months and with an average weight of 69.78 ± 8.81 kg were sampled in a 12-week experiment to evaluate the response of calves to supplementation of legume - based concentrate diets. These calves graze on natural pastures. The sampled calves were allotted in a completely randomised design into four treatment groups and offered 25% Leucaena leucocephala, Enterolobium cyclocarpum and Glricidia sepium based concentrate diets and natural pastures (control) for treatments 1 - 4 respectively. Data were collected on feed intake, weight gain, nutrient digestibility, nitrogen balance, blood profile and faecal egg count of calves. The supplementation of forage legume concentrate diets improved (P < 0.05) DM intake and weight gain of calves with best results were observed in calves fed Glricidia sepium concentrate diets with 450.56 g/day and 188.45 g/day respectively. Nutrient digestibility (%) and nitrogen balance varied (P < 0.05) across treatment groups. Blood parameters did not differ (P > 0.05) across treatments and falls within the normal range for healthy calves, while the supplementation of forage legume concentrate diets reduced (P < 0.05) faecal egg count (egg/g) to ascertain the level of worm burden in calves. The study concluded that supplementation with legume concentrate diets improved the performance of calves with Gliricidia forage supplemented concentrate diet recommended for calves’ optimum performance.